2020
DOI: 10.1016/j.scitotenv.2020.140278
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-detected tropospheric nitrogen dioxide and spread of SARS-CoV-2 infection in Northern Italy

Abstract: Air pollution might increase susceptibility to SARS-CoV-2 infection. • We examined infection prevalence in the most affected regions in Northern Italy. • Satellite-detected tropospheric nitrogen dioxide was used to assess air pollution. • High NO 2 levels were associated with spread of the infection. • A causal role remains speculative, given ecologic biases and uncontrolled confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 46 publications
(50 reference statements)
5
65
0
Order By: Relevance
“…They found a strong relationship between PM2.5 and death risk from COVID-19. Similar findings were reported regarding China ( Pansini and Fornacca, 2020 ; Xu et al, 2020a ; Yao et al, 2020 ; Yongjian et al, 2020 ; Zhang et al, 2020 ), Italy ( Fattorini and Regoli, 2020 ; Filippini et al, 2020 ; Zoran et al, 2020 ), England ( Travaglio et al, 2020 ), Netherlands ( Andree, 2020 ), France ( Magazzino and Schneider, 2020 ), Malaysia ( Suhaimi et al, 2020 ), Germany ( Ogen, 2020 ), and India ( Saha et al, 2020 ). The study conducted by Saha et al (2020) also reported that areas with better air quality showed a larger number of COVID-19 recoveries.…”
Section: Pollutants and Their Relationship To Covid-19supporting
confidence: 71%
“…They found a strong relationship between PM2.5 and death risk from COVID-19. Similar findings were reported regarding China ( Pansini and Fornacca, 2020 ; Xu et al, 2020a ; Yao et al, 2020 ; Yongjian et al, 2020 ; Zhang et al, 2020 ), Italy ( Fattorini and Regoli, 2020 ; Filippini et al, 2020 ; Zoran et al, 2020 ), England ( Travaglio et al, 2020 ), Netherlands ( Andree, 2020 ), France ( Magazzino and Schneider, 2020 ), Malaysia ( Suhaimi et al, 2020 ), Germany ( Ogen, 2020 ), and India ( Saha et al, 2020 ). The study conducted by Saha et al (2020) also reported that areas with better air quality showed a larger number of COVID-19 recoveries.…”
Section: Pollutants and Their Relationship To Covid-19supporting
confidence: 71%
“…Therefore, lockdown and movement restriction measures can improve air quality and avoid spread of infectious diseases (Coccia, 2020b;Fattorini and Regoli, 2020;Filippini et al, 2020;Lau et al, 2020;Pirouz et al, 2020;Shen et al, 2020;Zambrano-Monserrate et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These factors included medical history, life-style factors, and environmental risk factors such as climate indicators and air pollutants. Some studies suggested a possible relation of virus outbreak with high levels of environmental air pollution (Barcelo, 2020;Bashir et al, 2020;Copat et al, 2020;Filippini et al, 2020;Li et al, 2020;Ogen, 2020;Pequeno et al, 2020;Setti et al, 2020b;Tsatsakis et al, 2020;Wu et al, 2020;Zhu et al, 2020). Putative mechanisms included enhanced susceptibility to respiratory viral infections through damage and inflammation of lung cells, immune dysregulation, and hyperactivation of inflammatory cytokines and chemokines (Chen et al, 2010;Comunian et al, 2020;Conticini et al, 2020;Peng et al, 2020), upregulation of viral receptor ACE-2 (Borro et al, 2020;Tung et al, 2020), or air pathogen transportation by particulate matter suitable as virus carrier (Comunian et al, 2020;Manoj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%